Pola Komunikasi Orang Tua Single Mom dalam Membentuk Kemandirian Pada Anak - Muhammad Robith Ilma; Danang Tandyonomanu (Universitas Negeri Surabaya, 2025)
Children's Independence is the ability that exists within a child to think before acting, to be able to do something individually, and to be responsible for their obligations. This study aims to determine the communication patterns of the parenting of single mothers in forming independence in children. This study uses qualitative research by using a phenomenological method that studies events or phenomena that occur naturally. This study focuses on the communication patterns applied by single mothers to their children so that independence can be embedded and applied to the child's life in the future. The results of this study found that the communication patterns of single mothers play an important role in forming independence in children. Various strategies and communication patterns such as joint decision-making, teaching responsibility, time management, and learning emotional intelligence used by single mothers have proven effective in instilling independent traits and attitudes in children.